(3TQM GdeYdbGJ GdSHYs - (3MSjf Hf CMeO Hf MSjf GdRhRfj, CHh YHO Gddg,J (B486 (3g` s
(3ChdgG (B:s
(3bGd GdbGVi GdCeGe CHh YHO Gddg gPG TQM GdbUGFO GdSHY , CedjJg Ydi MO GdEjLGR hGdGNJUGQ Ydi MSH eG GbJQM Ydi s
(3BNQgG (B:s
(3hgh GdQH hGdTgjO Ydi jhe GdMjGQjf hGdHdGA HdGA Je GdcJGH HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HBNQ UaMGJgG JYbjHIs
(3fSNI SGHYI JJab ai ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa ai HYV GdCdaGXs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B231 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B309 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B310s
Keywords: (3GdCOHs